The Influence of add-on Service Innovation on Purchasing Decisions At Resorts and Villas in Ubud Mediated by the Behavioral Intention of Multigenerational Family Tourists - Deasy Astrid Natalia; Komang Agus Rudi Indra Laksmana; , I Gusti Ayu Diah Werdhi Srikandi (Indonesian Journal of Business Analytics, 2026)
The hospitality sector faces the intricate challenge of catering to the varied demands of multigenerational family tourists. Innovative ancillary services — or add-ons, encompassing cultural programs, cooking classes, spa packages, children's activities, and private transportation — emerge as a crucial differentiation strategy, significantly boosting perceived value and guest satisfaction. Employing a quantitative, causal research design using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, the research surveyed 90 multigenerational family tourists selected through purposive sampling. The results reveal that add-on service innovations significantly and positively influence both tourists' behavioral intention (β = 0.517; p = 0.000) and their purchasing decisions (β = 0.297; T = 2.751; p = 0.006). Furthermore, behavioral intention strongly predicts purchasing decisions (β = 0.457; T = 5.380; p = 0.000), and significantly mediates the relationship between add-on innovation and purchasing decisions (p = 0.000; T > 1.96). These findings align with Service-Dominant Logic (SDL) and the Theory of Planned Behavior (TPB), underscoring that strategic add-on innovation drives purchasing decisions both directly and indirectly through the formation of positive behavioral intentions.